Beyond the Usual: Understanding the Multidimensional Nature of Job Quality in Bolivia's Labor Market - Gustavo J. Canavire Bacarreza; Ronald A. Cueva; María E. Dávalos (Institute of Labor Economics (IZA), 2024)
Job quality can impact workers' productivity and contribute to societal well-being. To analyze the evolution of job quality in Bolivia, this paper employs Bolivian household survey data spanning 2007 to 2021 to construct a synthetic job quality index. The index incorporates a broad definition of a good job, encompassing six dimensions: adherence to regulations, working conditions, establishment of an appropriate wage-job linkage, productive usage and adaptability of skills, availability of career opportunities, and employment resilience. The findings indicate that job quality in Bolivia has mostly remained incessant, exhibiting limited change even during periods of high growth in economic output. However, this result masks heterogeneities, with significant variation in job quality associated with workers' demographic and job-specific characteristics and across regions.
Keywords: J21; J26; J28; J81; 330; labor market; principal component analysis; job quality; Bolivia